If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7x-1=2(x-2)
We simplify the equation to the form, which is simple to understand
-7x-1=2(x-2)
Reorder the terms in parentheses
-7x-1=+(+2x-4)
Remove unnecessary parentheses
-7x-1=+2x-4
We move all terms containing x to the left and all other terms to the right.
-7x-2x=-4+1
We simplify left and right side of the equation.
-9x=-3
We divide both sides of the equation by -9 to get x.
x=0.333333333333
| 5y-18=-54+y | | 2h-5=45 | | -4(-2+7x)=-244 | | 2-2x-8=0 | | 5,56*400*x=14178 | | -5x-1=x | | 29=4(2k-6) | | (-x^2)+(-.000018)+(.000003x)=0 | | 7n+2n=-35 | | -7c-8-5z=-32 | | -4(2+7x)=-244 | | 3+-3= | | 2x+7=12x-9 | | bx+c=y | | abx=ab | | (7k-1/3k)(1/1-7k) | | 5y-7x+3=0 | | 6y-9=3 | | 2/x=10/15 | | bx=m+n | | 5x-4y-11=0 | | 8x+12=10x-2 | | x-6=a | | f(4)=5x+4 | | 2m-10=50 | | 30=-30n+-30 | | 4x/3-5x/7=x-8 | | 2x-25=3x-15 | | 2m+5=50 | | -2[1-5(1+4x)]=-108-10x | | 2(m-5)=50 | | f(-4)=-5x-3 |